Cops, Cameras, and Crisis : The Potential and the Perils of Police Body-Worn Cameras - White, Michael D. (Michael Douglas), 1951-; Malm, Aili E. (Book collections on Project MUSE., 2020)
"Following the tragic deaths of Eric Garner, Michael Brown, and others at the hands of police, interest in body-worn cameras for local, state, and federal law enforcement has skyrocketed. In Cops, Cameras, and Crisis, Michael D. White and Aili Malm provide an up-to-date analysis of this promising technology, evaluating whether it can address today's crisis in police legitimacy. Drawing on the latest research and insights from experts with field experience with police-worn body cameras, White and Malm show the benefits and drawbacks of this technology for police departments, police officers, and members of the public. Ultimately, they identify--and assess--each claim, weighing in on whether the specter of being "caught on tape" is capable of changing a criminal justice system desperately in need of reform."--Publisher's description.